2021
DOI: 10.1002/adfm.202104427
|View full text |Cite
|
Sign up to set email alerts
|

Leather‐Based Multi‐Stimuli Responsive Chromisms

Abstract: Leather is made from the skin of animals and possesses special micro-and nanostructures. Due to the high breathability, durability, strength, elasticity, and softness, leather is widely used in daily life, and is an ideal substrate for future multi-functional wearable smart devices. Herein, two leather-based multistimuli responsive chromic devices denoted as UV/thermo/electro chromic device and UV sensor are developed. The UV/thermo/electro chromic device demonstrates instantaneous and reversible chromic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…[37] Huo et al [38] reported the flexible electronic skin (e-skin) with pressure sensing capabilities by integrating the carbon nanotubes (CNTs) with sophisticated leather substrate for human health monitoring. Jia et al [39] demonstrated the fabrication of multi-stimuli responsive chromic devices based on the leather treated with poly(styrene sulfonic acid) doped poly(3,4-ethylenedioxythiophene) (PEDOT:PSS). Shi et al [40] fabricated the lightweight and high-performance EMI shielding nanocomposites by coating metal nanoparticles (MNPs) onto leather.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Huo et al [38] reported the flexible electronic skin (e-skin) with pressure sensing capabilities by integrating the carbon nanotubes (CNTs) with sophisticated leather substrate for human health monitoring. Jia et al [39] demonstrated the fabrication of multi-stimuli responsive chromic devices based on the leather treated with poly(styrene sulfonic acid) doped poly(3,4-ethylenedioxythiophene) (PEDOT:PSS). Shi et al [40] fabricated the lightweight and high-performance EMI shielding nanocomposites by coating metal nanoparticles (MNPs) onto leather.…”
Section: Introductionmentioning
confidence: 99%
“…8,21,22 These intriguing attributes permit the development of various smart soft photonics or electronics, which can lead to widespread application, including, smart windows, 4,6,10,17 dynamic displays, 1,3,4,7,10,12 rewritable media, 1,3,4,6,7 anticounterfeit tabs, 1,4,6,7 encryption devices 1,4,6,9,10,13 stretchable electronics, 2,5,15 wearable strain sensors, 2,5,6,[10][11][12]15,18 human−machine interface, 2,5 thermal camouflage, 13 humidity sensors, 1,4,6,9 and so on. 8,19,21 The design of such captivating materials has been largely inspired by natural life, particularly the multiscale structure, adaptive mechanism, and dynamic response, which are widely manifested in the animal or plant kingdoms. Thus, one of the most widely adopted efforts in smar...…”
Section: Introductionmentioning
confidence: 99%
“…The physical and/or chemical characteristics of smart soft materials can be dynamically converted when subjected to external stimuli, such as light, solvent, ,, mechanical strain, , temperature, , ,,, electric and/or magnetic fields, ,,, and so on. ,, These intriguing attributes permit the development of various smart soft photonics or electronics, which can lead to widespread application, including, smart windows, ,,, dynamic displays, ,,,,, rewritable media, ,,,, anticounterfeit tabs, ,,, encryption devices ,,,,, stretchable electronics, ,, wearable strain sensors, ,,, ,, human–machine interface, , thermal camouflage, humidity sensors, ,,, and so on. ,, The design of such captivating materials has been largely insp...…”
Section: Introductionmentioning
confidence: 99%
“…2 Currently, blue and green persistent luminescence phosphors have been welldeveloped and commercialized due to their excellent performance, [3][4][5][6][7][8] but persistent luminescence materials of other colors are still being developed in the laboratory due to their difficult synthesis and poor performance. Colorful spectra will open up opportunities for persistent luminescence materials for applications, especially in new types of light sources, 8,9 optoelectronic devices, [10][11][12] individual customization, 13,14 and advanced information security/information anticounterfeiting. [15][16][17] Therefore, the development of color-tunable photoluminescence materials has important scientific significance and practical value but remains challenging.…”
Section: Introductionmentioning
confidence: 99%